The intensity of carbohydrate metabolism in the body of sows under the action of ferrum and germanium nanocompounds - O. O. Kovalchuk; V. A. Tomchuk; V. O. Danchuk; P. S. Khymynets; B. V. Gutyj; S. V. Kravchuk; O. V. Zhurenko; D. I. Kryvoruchko; V. V. Karpovskyi; P. V. Karpovskyi; V. B. Todoriuk; R. V. Hrelia; et al. (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article shows the influence of ferrum and germanium nanoparticles on the indicators of carbohydrate metabolism in sows' blood before and after farrowing. The impact of farrowing on the content of glucose, lactate, pyruvate, and lactate dehydrogenase activity in the blood plasma of animals was established (F= 9.0–38.7 > FU = 2.9; P < 0.001). By the day of farrowing, the blood glucose content of sows increases by 14.8 % (P ≤ 0.05), lactate by 30.1 % (P ≤ 0.001), pyruvate by 15.4 % (P ≤ 0.05), lactate dehydrogenase activity by 18.0 % (P ≤ 0.05). Within ten days after farrowing, the content of glucose in the blood serum of sows decreases by 17.1 % (P ≤ 0.05), the content of lactate decreases by 25.0 % (P ≤ 0.001), and the activity of lactate dehydrogenase by 22 % (P ≤ 0.001). Administration of iron and germanium nanocompounds for ten days had a significant effect on lactate content and lactate dehydrogenase activity in the blood of sows – F= 8.6–10.9 > FU = 4.15 (Р = 0.002–0.006). One day before farrowing, the lactate content in the blood plasma of sows was 17.0 % (P ≤ 0.05) lower; due to doda, after farrowing, the content of lactate was lower by 12.6 % (P ≤ 0.05), and pyruvate by 8.4 % (P ≤ 0.05) more than the indicators of animals of the control group. The most significant effect of the application of nanocompounds of iron and germanium on indicators of hydrocarbon metabolism in the blood of sows was revealed during the day after farrowing; in particular, the effect of the application of nanoparticles on the content of lactate, pyruvate, and their ratio in the blood of sows was – ħ²ᵪ=0.53–0.71 (P ≤ 0.05–0.01). Three days after farrowing, administration of metal nanoparticles affects lactate dehydrogenase activity in sows' blood (ħ²ᵪ = 0.46; P ≤ 0.05).